2019
DOI: 10.1038/s41598-019-44476-w
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of erythrocyte membrane polyunsaturated fatty acids in preterm newborns with retinopathy of prematurity

Abstract: Extremely preterm infants are at high risk for retinopathy of prematurity (ROP), a potentially blinding disease characterized by abnormalities in retinal vascularization. Whereas animal studies revealed that n-3 polyunsaturated fatty acids (PUFAs) may be of benefit in preventing ROP, human studies conducted on preterm infants during the 1 st weeks of life showed no association between blood n-3 PUFA bioavailability and ROP incidence and/or severity, probably because of the influence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 58 publications
6
23
1
Order By: Relevance
“…By contrast, intravenous administration of fish-oil-based lipid emulsion (SmofLipid ® , Fresenius Kabi), a blend of plant- and animal-based lipid emulsions with a higher n-6/n-3 fatty acids ratio than in the diet, resulted in less ROP but did not alter the requirement for laser treatment or the ROP frequency [ 119 , 120 ]. These conflicting results may stem from the optimal ratio of n-6 fatty acids, such as AA, to n-3 fatty acids for the developmental stage in preterm infants [ 121 ]. Recent randomized controlled clinical trials have studied the effect of n-3 fatty acid or a combination of DHA and AA on ROP outcome and may help to solve these problems (ClinicalTrials.gov Identifier: NCT02486042, NCT03201588).…”
Section: Pathology Of Retinopathy Of Prematurity (Rop) and Its Relmentioning
confidence: 99%
“…By contrast, intravenous administration of fish-oil-based lipid emulsion (SmofLipid ® , Fresenius Kabi), a blend of plant- and animal-based lipid emulsions with a higher n-6/n-3 fatty acids ratio than in the diet, resulted in less ROP but did not alter the requirement for laser treatment or the ROP frequency [ 119 , 120 ]. These conflicting results may stem from the optimal ratio of n-6 fatty acids, such as AA, to n-3 fatty acids for the developmental stage in preterm infants [ 121 ]. Recent randomized controlled clinical trials have studied the effect of n-3 fatty acid or a combination of DHA and AA on ROP outcome and may help to solve these problems (ClinicalTrials.gov Identifier: NCT02486042, NCT03201588).…”
Section: Pathology Of Retinopathy Of Prematurity (Rop) and Its Relmentioning
confidence: 99%
“…Concerning the effects of n-3 PUFA supplementation on ROP in preterm infants, no final conclusions have yet been reached. In a prospective cohort study, it is found that a time-dependent accumulation of AA at the expense of DHA seems to occur in utero in erythrocytes of preterm infants who will develop ROP, thus reinforcing the beneficial properties of DHA on this disease [ 28 ]. In other observational or prospective randomized studies, the use of intravenous fish oil-containing lipid emulsions is associated with a lower incidence of ROP or severe ROP and decreased need for laser or bevacizumab treatment in preterm infants [ 29 31 ], which is in keeping with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for the choice of 10 fatty acids takes into account the most representative components in terms of structural and functional roles played by such hydrophobic moieties in membrane phospholipids, as well as the nutritionally important PUFAs (see Figure 1). We arbitrarily chose this cohort for the application to veterinary analyses, taking into consideration our and others' work done in humans with physiological and pathological conditions (15)(16)(17)(18)(25)(26)(27)(28). It is worth underlining that studies reported in literature on fatty acids of erythrocyte membranes in both humans and animals do not report the same cohort of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, we contributed to research in membrane fatty-acid-based lipidomics, making the arbitrary choice of analyzing a specific fatty acid cohort of erythrocyte membrane glycerophospholipids, made of 10 fatty acids representative of SFA, MUFA, and PUFA families. Their interval values in healthy cohorts were reported in membrane fatty acids by several studies, also by us (25)(26)(27), and in one of the most complete metaanalysis appeared in the literature (28). Taking into account that novel fatty acid pathways and transformations are continuously studied (29), it is important to make the strategic choice of a specific number of fatty acids considering their fundamental biochemical/biological roles and the consensus reached about their levels in cell membranes.…”
Section: Introductionmentioning
confidence: 95%